MORPHOLOGICAL FEATURES OF CRYSTALLINE STRUCTURES FORMED DURING DEHYDRATION OF HUMAN SALIVA UNDER CONTROLLED EXPERIMENTAL CONDITIONS - Ergashev , Erkinjon; Mashrabboyev , Abdusamad; Abdug‘aniyev , Asadbek (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
Background: Human saliva is a complex biological fluid whose dehydration leads to the redistribution of dissolved and colloidal components, forming characteristic crystalline and amorphous structures. Objective: To investigate the morphological features of crystalline structures formed during controlled dehydration of human saliva. Methods: Unstimulated saliva samples (4 µL droplets) were collected from 10 healthy male volunteers aged 18–30 years and dehydrated at 25 °C and 32% relative humidity for 25–30 minutes. Digital microscopy (50×–200×) was used for morphological assessment, evaluating crystal shape, dendritic branching, zonal organization, density, symmetry, and structural heterogeneity. Results: Dehydrated saliva droplets formed structurally organized and morphologically heterogeneous patterns with distinct peripheral and central zones. Dendritic, branched, radiating, and irregular crystal forms were observed. Peripheral zones exhibited relatively ordered radial structures, while central zones displayed denser, highly branched formations. Conclusions: Saliva dehydration involves complex phase-structural transformations rather than simple drying, producing reproducible crystalline patterns that reflect internal fluid organization. These findings provide a methodological basis for comparative studies involving external modifying factors.